Molecular engineering of intrinsically microporous polybenzimidazole for energy-efficient gas separation. (March 2022) - Abdulhamid, Mahmoud A.; Hardian, Rifan; Bhatt, Prashant M.; Datta, Shuvo Jit; Ramirez, Adrian; Gascon, Jorge; Eddaoudi, Mohamed; Szekely, Gyorgy
Highlights: Synthesis of intrinsically microporous polybenzimidazole (iPBI) and its crosslinked counterpart (x-iPBI). Unprecedented enhancement in BET surface area after replacing the flat benzene ring with a kinked moiety. Enhancement in size-sieving properties by crosslinking. High potential for CO2 capturing and storage. 70% energy reduction upon using iPBI relative to conventional technologies. Abstract: Polybenzimidazole (PBI) is a high-performance polymer that exhibits high thermal and chemical stability. However, it suffers from low porosity and low fractional free volume, which hinder its application as separation material. Herein, we demonstrate the molecular engineering of gas separation materials by manipulating a PBI backbone possessing kinked moieties. PBI was selected as it contains NH groups which increase the affinity towards CO2, increase sorption capacity, and favors CO2 over other gasses. We have designed and synthesized an intrinsically microporous polybenzimidazole (iPBI) featuring a spirobisindane structure. Introducing a kinked moiety in conjunction with crosslinking enhanced the polymer properties, markedly increasing the gas separation performance. In particular, the BET surface area of PBI increased 30-fold by replacing a flat benzene ring with a kinked structure. iPBI displayed a good CO2 uptake of 1.4 mmol g −1 at 1 bar and 3.6 mmol g −1 at 10 bar. Gas sorption uptake and breakthrough experiments were conducted using mixtures of CO2 /CH4 (50%/50%) and CO2 /N2 (50%/50%), which revealed the high selectivity of CO2 over both CH4 and N2 . The obtained CO2 /N2 selectivity is attractive for power plant flue gas application requiring CO2 capturing materials. Energy and process simulations of biogas CO2 removal demonstrated that up to 70% of the capture energy could be saved when iPBI was used rather than the current amine technology (methyl diethanolamine [MDEA]). Similarly, the combination of iPBI and MDEA in a hybrid system exhibited the highest CO2 capture yield (99%), resulting in nearly 50% energy saving. The concept of enhancing the porosity of PBI using kinked moieties provides new scope for designing highly porous polybenzimidazoles for various separation processes. Graphical abstract: Image, graphical abstract